Penetapan Sertifikat Hak Milik Tanah Elrektronik dalam Sistem Hukum Indonesia - Muhimmatul Hidayah; Nana Eka Wijayanti; Salsabilla Zahra Sanda; Sumriyah Sumriyah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Thanks to rapid technological advances, it is increasingly easier to provide services to the public. One example is the electronic land certificate service. The time and costs of registering land certificates can be reduced by using the latest technological methods. The research method used by the author is a statutory approach and normative research methods. The research results show that significant technological progress can be made by digitizing the current paper-based land registration system. One of them is the issuance of electronic certificates as regulated in Regulation of the Minister of ATR/Head of BPN No. 1 of 2021 because the Electronic Transaction Information Law and the Job Creation Law only regulate electronic certificates, this electronic certificate is legal and the risk of causing problems is very small. Technology supporting the use of electronic land title certificates is developing rapidly and is now very useful. As an institution that provides electronic services in the land sector, BPN not only improves data quality control, but also continues to improve electronic services with professional staff. The implementation of land title certificates still has shortcomings in terms of infrastructure, equipment, human resources and electronic data quality.